Analytical Study of Cylindrical Channels in Dense Layers - Saparov Bobur Jumaboevich; Tavbaev Jumaboy Saparovich (Genius Journals, 2022)
The paper presents the formulation of the boundary value problem of a thin channel in a boiling distance near the free surface. The modified boundary layer method is used to obtain an analytical solution of the boundary value problem for measuring the fraction and determining the crosslinking
Keywords: Fluidized bed; catalyst; reactor; reagent